Answers

2016-07-15T09:18:30+08:00
(x+3)³ = x³+9x²+27x+27 First step : (x)(x)(x) or (x)³ = x³ Second = (3)(x)² = 9x². Ung pangalawang sagot ang laging ii-Square. Third : (3)(x)³ = 27x How?. (3)(3) = 9(3) = 27(x) = 27x Forth : (3)³ = 27 How?. (3)(3)=9(3) = 27 The answer is x³+9x²+27x+27
0
  • Brainly User
2016-07-15T14:33:42+08:00
(a + b)³   where a is the first term, and b is the second term.

Ex:  (2x + 3y)³  where 2x is the first term, and 3y is the second term

Step:
1)  Cube the first term: (2x)³ ⇒ (2x)(2x)(2x) = 8x³

2) 3(first term)² (second term) ⇒ 3(2x)²(3y) = 3(4x²)(3y) = 36x²y

3) 3 (first term) (second term)² ⇒  3(2x)(3y)² = 6x (9y²) = 54xy²

4) Cube the last term: (3y)³ = (3y)(3y)(3y) = 27y³

Answer: 8x³ + 36x²y + 54xy² + 27y³
0